Texture Profile Analysis of Lamtoro Gung (Leucaena leucocephala ssp. Glabrata (Rose) S. Zarate) Tempeh - Fitriani, Aprilia; Haliza , Miftah Nur; Utami , Nurul Putrie; Nyambayo, Isabella; Sanayei, Sanaz; Rahmadhia, Safinta Nurindra (Journal of Agri-Food Science and Technology, 2024)
Lamtoro Gung seeds are low in fat content but rich in protein. Lamtoro Gung is often used as an alternative protein source. Lamtoro Gung is usually taken as a prepared meal containing grains and nuts. It is germinated and utilized in a variety of dishes, including the production of tempeh. However, nothing has been done to explain the textural profile of Lamtoro Gung tempeh, which is made by fermentation processes in various packaging materials such as plastic, banana leaves, and teak leaves. This study aims to evaluate the textural characteristics of Lamtoro Gung tempeh produced using different packaging materials and fermentation periods. This study contributes to understanding how packaging variations affect the texture of Lamtoro Gung tempeh. Tempeh made from teak leaf packaging and fermented for four days offered better texture profile hardness (195.38 N), cohesiveness (0.46), gumminess (81.57 N), and chewiness (54.99 N) higher than banana leaves; hardness (49.90 N), cohesiveness (0.29), gumminess (14.52 N), and chewiness (10.14 N) but similar to plastic; hardness (165.28 N), cohesiveness (0.45), gumminess (74.23 N), and chewiness (50.35 N). Therefore, packaging material impacts the texture profile of tempeh fermented from Lamtoro Gung seeds. Sensory evaluation of the tempeh would need to be investigated to check consumer acceptance of the product.